A Study of the Impact of Peer Review on Academic English Writing among English Majors - Ma Jiayue (SHS Web of Conferences, 2023)
Peer review is a hot topic in the research of writing teaching for English majors. At present, there is still great controversy in the academic community about its feasibility and effect. To fully sort out the impact of peer feedback on different contents in English writing, grasp its advantages and disadvantages in teaching, and put forward some implementable suggestions to improve teaching and make peer feedback better serve the teaching, this study used semi-structured interviews as the main method and questionnaires as the supplemented survey to survey eight students majoring in English in a university of foreign languages in Northeast China. The study founds that peer review mainly includes mutual evaluation of nine parts, such as vocabulary, grammar, punctuation, sentence coherence, and article structure, and mainly focuses on the surface content of language, such as vocabulary, grammar, punctuation, etc. In addition, the study found that despite some shortcomings, peer feedback is still a promising way to 2nd language writing feedback, which can enhance students’ critical thinking skills and many other abilities. Research shows that we should actively incorporate peer feedback in college English writing classes to fully exploit its teaching potential in English writing.